2019
DOI: 10.1177/0145445519880837
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Skills Training to Increase Appropriate Reactions of Adolescent Males in Residential Treatment

Abstract: Adolescents in secured residential facilities may engage in excess behavior immediately following verbal directives or corrective statements from staff. Excess behavior may include verbal aggression, indices of disrespect (e.g., eye rolling, grunting, and obscene gestures), or even physical aggression. These excess behaviors may evoke further directives or corrective statements from staff that, in turn, escalate the adolescent’s excess behavior and can produce undesirable effects for both the adolescent (e.g.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…The present study also included an error analysis for identifying specific segments of the more complex skill that were particularly difficult for these students. This study also extends the literature on the use of behavior analytic procedures to address behavioral deficits and excesses displayed by adolescents in residential juvenile facilities (e.g., Brogan et al, ; Brogan, Falligant, & Rapp, ; Brogan, Rapp et al, ; Niedfeld et al, ).…”
Section: Discussionsupporting
confidence: 73%
“…The present study also included an error analysis for identifying specific segments of the more complex skill that were particularly difficult for these students. This study also extends the literature on the use of behavior analytic procedures to address behavioral deficits and excesses displayed by adolescents in residential juvenile facilities (e.g., Brogan et al, ; Brogan, Falligant, & Rapp, ; Brogan, Rapp et al, ; Niedfeld et al, ).…”
Section: Discussionsupporting
confidence: 73%
“…Results for descriptive assessments suggested residents lacked the skill to receive feedback from staff members. To address this gap, Brogan et al ( 2021 ) taught students to engage in an appropriate verbal response (e.g., “Yes/No, ma’am/sir”) when presented with directions or corrective statements from staff members. The intervention included all of the components of behavioral skills training (BST) before a 10-trial session during which ABA team members delivered feedback for correct and incorrect responses.…”
Section: Behavioral Interventions For Individual Studentsmentioning
confidence: 99%
“…Therefore, this review focuses on the 10 identified intervention research studies aimed at improving the behavior of youth in JCF (see Table 1). Specific to the current systematic review, results of the electronic search resulted in identifying two relevant studies (i.e., Brogan et al, 2017; Edgemon et al, 2020), while the hand search led to the inclusion of another eight studies (i.e., Brogan et al, 2020; Chinnappan et al, 2020; Hamrick et al, 2020; Knight et al, 2019; Lively et al, 2019; McDougale et al, 2019 (two studies in one article); O’Rourke et al, 2020). Overall, included studies came from a small number of research journals, including Behavior Modification ( n = 7), Journal of Applied Behavior Analysis ( n = 1), Criminal Justice and Behavior ( n = 1), and The Journal of Correctional Education ( n = 1)…”
Section: Thematic Coding Processmentioning
confidence: 99%
“…Therefore, this review focuses on the 10 identified intervention research studies aimed at improving the behavior of youth in JCF (see Table 1). Specific to the current systematic review, results of the electronic search resulted in identifying two relevant studies (i.e., Brogan et al, 2017;Edgemon et al, 2020), while the hand search led to the inclusion of another eight studies (i.e., Brogan et al, 2020;Chinnappan et al, 2020;Hamrick et al, 2020;Knight et al, 2019;Lively et al, 2019;McDougale et al, 2019 (two…”
Section: Thematic Coding Processmentioning
confidence: 99%
See 1 more Smart Citation